Shariah audit in Islamic financial institutions: The effects of spirituality and moderating role on judgement and decision making / Yazkhiruni Yahya - Yazkhiruni, Yahya (2016)
Auditing in the Islamic framework or also known as Islamic auditing has a wider scope than the current practice of auditing. Main objective of auditing from the Islamic perspective is to embrace the Maqasid As – Shariah (Objective of Islamic Principles) as well as to uphold the shariah principles in all practices and process. Shariah auditing requires auditors to judge whether the process and outcomes of audit comply with the Islamic principles, which have a far-reaching implication beyond the usual attestation of current practices of auditing that is to give attestation, assurance of financial statement and internal control of the institutions is adequately safeguarded and protected. The Central Bank of Malaysia in Shariah Governance Framework specified that shariah audit should be conducted by internal auditors. This study has three objectives and has been undertaken through qualitative phase (interview) and quantitative phase (experiment). For first objective, this study attempts to investigate the types of knowledge required during shariah auditing process in IFIs. Research data for this exploratory stage is obtained from 15 semi - structured interviews conducted with the chief internal auditors of IFIs, shariah committee, academicians, bankers, external auditors and regulators. It is discovered that, the IBF, shariah knowledge and internal audit knowledge are essential to be acquired by internal auditors during shariah auditing process. Then, second objective of this study is to identify whether spirituality has significant effects towards shariah auditing judgment performance. Furthermore, the third objective of the study investigated the moderating effects identified as task complexity, knowledge and ethics, which are recognized as ‘Determinants of Performance’ towards shariah audit judgment performance. The Social Cognitive Theory (SCT) is used to explain the influence of spirituality and moderating variables towards shariah auditing judgement performance. To date, current discourse of shariah audit by internal auditors is limited in which its role, function, and implementation in IFIs has not been fully addressed. Moreover, research in the field of spirituality and judgment decision making (JDM) focusing on internal auditors’ judgment in real practices is relatively new compared with the development of spirituality and judgment decision making involving external auditors. Therefore, the study contributes to the literature on how spirituality has implication on JDM. A total of 146 internal auditors participated in the experiments. The results reported that spirituality influenced internal auditors’ shariah audit judgment performance. Then, the findings from the experiments, which tested the moderating effects, identified i.e. task complexity, knowledge and ethics produced mixed results. Of all the three moderators, task complexity was deemed significant towards relations between spirituality and shariah audit judgment performance. In contrast, knowledge and ethics did not seem to have a significant moderating influence on the spirituality and shariah audit judgment performance. The interviews complemented experiment’s design as well as interpretation of results. Finally, the findings may have some implications for regulators and others concerned with establishing guidelines, rules and knowledge requirements pertaining to shariah auditing practices. As such, practitioners might include spirituality as one of the important factors to increase quality of JDM process and shariah auditing process.